Exploring the Role of Union Digital Center to Managing Information Services in Rural Development of Bangladesh (Bangladesh Journal of Public Administration, 2020)
The information services are multidimensional and socially acts as the building block of communication among diverse groups in rural society. Rural development mostly relies on the effective use of information services in the day-to-day activities of rural people and rural administrations. In rural areas of Bangladesh, Union Digital Centre comprised of every prospect of delivering the advantages of new communication technologies towards the agricultural community who lagged behind the access to technology in their workplace, household social living, or at the institution. Prior studies revealed that the rural people of Bangladesh mostly suffer because of low productivity; the deterioration of social and economic conditions originated from the unavailability of adequate information. This article attempted to explore an overview of the roles of Union Digital Centre among various socio-politico-economic components in developing rural areas of Bangladesh. A convenience sampling technique was used to collect data through a structured questionnaire and a total of 100 respondents were selected from three old rural regions of Bangladesh. Besides, case study, focus group discussion, informal interviews, and content analyses were made. At the end, this paper discusses some findings on the importance of free access to technology for rural society, challenges, and recommendations that may guide policymakers and stakeholders.